The influence of thermophoresis and Brownian motion on maxwell nanofluids utilizing Cattaneo-Christov double diffusion theory - Akhtar Ali; Muhammad Ali; Majid Hussain; Irfan Ali; Amsalu Fenta (Advances in Mechanical Engineering)
The primary objective of this work is to examine the concentration and temperature boundary layers in a Maxwell nanofluid containing nanoparticles, influenced by thermophoresis & Brownian motion. The main findings are to enhance understanding of nanoscale heat with mass transport mechanisms, with potential applications in advanced thermal management systems and nanofluid-based technologies. The contribution of Cattaneo-Christov double diffusion theory captures time-delayed thermal effects. A system of partial differential equations (PDEs) is transformed into ordinary differential equations (ODEs) using similarity transformation (ST). The analysis considers the collective impacts of thermophoresis, Brownian motion, and viscoelasticity. The study elucidates the complex relationship between double diffusion phenomena and nanofluid behavior through analytical and numerical techniques. Dimensionless mathematical problems are numerically solved using MATLAB’s built-in function bvp4c, with the behavior of flow-controlling parameters presented through graphical and tabular data.